Pengembangan Modul Menulis Teks Fabel Berbasis Picture and Picture pada Siswa Kelas VII MTs Al-Bukhary Rantauprapat - Yuannisah Aini Nst; Saprida Saprida; Eko Firman Susilo (Departement of Mathematics Education, 2023)
This study discusses the development of picture and picture-based fable text writing modules in class VII students of MTs Al-Bukhary Rantauprapat. This type of research is development with a 4-D development model. The development steps carried out by the researcher are 1) the definition stage (define), 2). Design stage (design), 3). Stage of development (development), 4) Stage of deployment (disseminate). This study designed learning modules and administered tests to determine the ability to write fable texts. The instruments used in this study were media expert and material expert validation questionnaires, teacher and student response questionnaires and tests of the ability to write fable texts. After the module is made, the module for writing fable text based on picture and picture is validated by the expert. The validation was carried out by media experts and material experts so that the module for writing fable texts based on picture and picture was declared feasible for testing. The trial was carried out by asking for responses from teachers and students as research subjects. From the results of the post-test conducted at the end of the learning activity, it was obtained 90.3%, the student scores reached the minimum completeness criteria very well. And the results of the student response questionnaire analysis show the